Symmetrical dimer of the human dopamine transporter revealed by cross-linking Cys-306 at the extracellular end of the sixth transmembrane segment - Hastrup, Hanne (The National Academy of Sciences, 2001)
There is evidence both for and against Na(+)- and Cl(−)-dependent neurotransmitter transporters forming oligomers. We found that cross-linking the human dopamine transporter (DAT), which is heterologously expressed in human embryonic kidney 293 cells, either with copper phenanthroline (CuP) or the bifunctional reagent bis-(2-methanethiosulfonatoethyl)amine hydrochloride (bis-EA) increased the apparent molecular mass determined with nonreducing SDS/PAGE from ≈85 to ≈195 kDa. After cross-linking, but not before, coexpressed, differentially epitope-tagged DAT molecules, solubilized in Triton X-100, were coimmunoprecipitated. Thus, the 195-kDa complex was a homodimer. Cross-linking of DAT did not affect tyramine uptake. Replacement of Cys-306 with Ala prevented cross-linking. Replacement of all of the non-disulfide-bonded cysteines in the extracellular and membrane domains, except for Cys-306, did not prevent cross-linking. We conclude that the cross-link is between Cys-306 at the extracellular end of TM6 in each of the two DATs. The motif GVXXGVXXA occurs at the intracellular end of TM6 in DAT and is found in a number of other neurotransmitter transporters. This sequence was originally found at the dimerization interface in glycophorin A, and it promotes dimerization in model systems. Mutation of either glycine disrupted DAT expression and function. The intracellular end of TM6, like the extracellular end, is likely to be part of the dimerization interface.